(3GdYHbGJ GdYfHQjI aj WHbGJ GdLYaQjIs - (3Bd cGTa GdZWGA, eMeO MSjf Hf Ydj Hf GdQVG Hf ehSi Hf LYaQ, J (B1373 (3g`s ((3MSf Hf LGSe GdaMGes)
(3ChdgG (B:s
(3GdMeO ddg GdPj jUWaj ef YHGOg eG jTGA(B...(3hHYO, ajbhd GdYHO eMeO GdeOYh HGdMSjf(B...s
(3BNQgG (B:s
(3GdMGL ejQRG MSjf(B... (3aEfg TQa efRdfG djdI ef djGdj TgQ QeVGf(B... (3hdc GdZQV ef Pdc eG PcQJg aj UOQ GdQSGdI(B... (3hEdi gfG Jec GdLRA GdChd GdeTJedI Ydi GdWHbI GdChdi(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B256s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs